Reviving businesses with new organizational change management strategies - Geada, Nuno, 1983-; Anunciação, Pedro Fernandes, 1967- (Advances in logistics, operations, and management science (ALOMS) book series., 2021)
"This book analyzes the sensitivity of organizations to change management based on methodologies and tools to control impacts and investigates how employees are impacted by their environment discussing issues such as technology communication and business continuity and the importance of collaborative and interactive relationship pertaining to change management"--